Demonstration of the route of embryo migration in retroperitoneal ectopic pregnancy using contrast‐enhanced computed tomography. Issue 3 (26th November 2013) - Liang, Changhu; Li, Xueli; Zhao, Bin; Du, Yinglin; Xu, Shifeng
Abstract Retroperitoneal abdominal pregnancy is exceptionally rare. An unusual retroperitoneal pregnancy has a high risk of severe bleeding. Abdominal ultrasonography and whole abdominal computerized tomography scanning should be performed for the early diagnosis of ectopic pregnancy. A case of retroperitoneal ectopic pregnancy located very close to large retroperitoneal blood vessels and treated with resection is presented. Many unusual features of retroperitoneal ectopic pregnancy were highlighted as providing further evidence in support of the main proposed embryo migration mechanism via lymphatic vessels.